An inertizing and cooling process for grapes cryomaceration - Carillo, Maria; Formato, Andrea; Fabiani, Andrea; Scaglione, Giampiero; Pucillo, Giovanni Pio (Electronic Journal of Biotechnology, 2011)
Background: With this research an inertizing and cooling process for grapes cryomaceration has been set up. The process in question has been performed by an innovative plant that cooled the grapes rapidly in about 8 sec until they reached the set cryo-maceration temperature, using direct injection of liquid CO2. It works with a grape flow of approximately 2-3 tons/h, with a maximum thermal gradient of 20 K between the grape inlet and outlet temperature. For this plant a vibrating device was set up that allowed that only one grape cluster layer to be formed on the ribbon conveyor after the grapes had been put into the feedbox. A numerical model was set up for the cooling tunnel, and numerical simulations were performed to investigate the operative parameters of the machine in question. The numerical results were validated by means of experimental tests. Results: The wines obtained by using the considered plant (IW) were chemically analysed, and a comparison was performed with wines obtained with the same grape without the use of the plant (TW). All phenolic parameters were higher in IW wines, while other substances such as alcohol, reducing sugars, acids, and volatile acidity were less affected by the different winemaking technique. A deeper yellow colour was a direct consequence of the higher phenolic content of IW wines. Panelists preferred the IW wines, which had a richer, more delicate aroma. Conclusions: The study showed that careful exclusion of air combined with preventing oxidation during the cooling process, that is realized with the considered innovative cooling plant, effectively yields pleasing wines with more character.